Empowering Gen Z In Millennial Agricultural Development - Haryanta, Dwi; Maryoni, Hamdi Sari; Rozci, Fatchur (Journal of Applied Plant Technology, 2025)
A significant problem is the lack of interest among Indonesian youth in pursuing careers in agriculture, which has profound implications for the nation's food security and economic stability. This research aims to identify agricultural development strategies that appeal to millennials and Generation Z to ensure food self-sufficiency, achieve a sustainable agricultural system, and reduce unemployment. Data sources for the research included academic journals, books, research reports, and articles published in scientific databases such as Google Scholar, Scopus, IEEE Xplore, and ScienceDirect. Inclusion and exclusion criteria were applied to ensure that only relevant and high-quality literature was included in the analysis. Agricultural development strategies to attract millennials or Generation Z include technology-based agricultural development, particularly digital technology, entrepreneurship-based agricultural development, sustainable agricultural systems, community-based and collaborative agriculture, and market-oriented agricultural product development. The implications of the research findings for education and policymakers are to avoid introducing millennials or Generation Z to conventional agriculture, which has been viewed negatively and unattractively, and to instead introduce them to a millennial-centered agriculture (oriented towards Generation Z's agricultural needs)